Progresivitas State Auxiliary Organ dalam Resolusi Omission Pemerintah Daerah: Studi Efektivitas Intervensi Ombudsman Pada Tata Kelola Pelayanan Persampahan di Kabupaten Bangka Selatan - Kgs Chris Fither (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2026)
The phenomenon of omission (failure to act) by the local government of South Bangka Regency in providing waste management services represents a critical challenge to public service integrity. This research evaluates the effectiveness of the Ombudsman of the Republic of Indonesia’s non-judicial intervention in addressing structural waste management failures that violate citizens' constitutional rights to a healthy environment. Employing a normative-juridical legal research method through statutory and conceptual approaches, this study utilizes primary legal materials consisting of regulations and the Ombudsman's Systemic Review investigation documents (2025–2026). The results prove that the omission in the region constitutes maladministration, specifically a failure to provide services and neglect of legal obligations, violating the General Principles of Good Governance. Facing this bureaucratic impasse, the Ombudsman’s Systemic Review intervention proved effective as a progressive legal instrument. The implementation of seven corrective suggestions by the local government successfully transformed three legal system pillars at the local level: substance (drafting local regulations), structure (establishing a Technical Implementation Unit for Waste Management), and legal culture (decentralizing village fund allocation and integrating environmental education). Non-judicial oversight by a state auxiliary organ is highly effective in compelling bureaucratic compliance and restoring public service obligations systematically without resorting to rigid formal court litigation.